The impact of 8-week re-training following a 14-week period of training cessation on Greco-Roman wrestlers - Demirkiran, B.; Isin, A.; Sungur, Y.; Melekoglu, T. (PLOS ONE, 2025)
Background This study aimed to examine the changes in physical and physiological conditions in elite wrestlers from the Turkish National Wrestling Team, who experienced 14 weeks of restricted physical activity during the COVID-19 lockdown, followed by an 8-week period of retraining and competition.